2023
DOI: 10.3390/ma16083117
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of Different Pre-Treatment Techniques and 3D Printed Turbulence Promoter to Mitigate Membrane Fouling in Dairy Wastewater Module

Abstract: This study investigates the enhancement of dairy wastewater treatment using chemical and physical pre-treatments coupled with membrane separation techniques to reduce membrane fouling. Two mathematical models, namely the Hermia and resistance-in-series module, were utilized to comprehend the mechanisms of ultrafiltration (UF) membrane fouling. The predominant fouling mechanism was identified by fitting experimental data into four models. The study calculated and compared permeate flux, membrane rejection, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 51 publications
(57 reference statements)
0
1
0
Order By: Relevance
“…Another possible drawback is the quality and durability of the printed devices [85]. A third possible drawback is the environmental impact of 3D printing [86,87]. However, Tsai et al [88] concluded that the use of 3D-printed turbulence promoters is a simple alternative to increase the permeate flux through the membrane up to 78 % and that 3D printing technology provides significant progress in designing turbulence promoters with complex geometric shapes.…”
Section: Honeycomb Spacer (Or Crimped Net)mentioning
confidence: 99%
“…Another possible drawback is the quality and durability of the printed devices [85]. A third possible drawback is the environmental impact of 3D printing [86,87]. However, Tsai et al [88] concluded that the use of 3D-printed turbulence promoters is a simple alternative to increase the permeate flux through the membrane up to 78 % and that 3D printing technology provides significant progress in designing turbulence promoters with complex geometric shapes.…”
Section: Honeycomb Spacer (Or Crimped Net)mentioning
confidence: 99%